THE DYNAMICS OF CREATIVITY, MOTIF AESTHETICS, AND FUNCTIONAL TRANSFORMATION IN JEPARA'S RAMAYANA WOOD CARVING RELIEFS - Inez Safitri; Wasis Wijayanto (Universitas Negeri Semarang, 2025)
Jepara wood carving, as a world intangible cultural heritage, currently faces serious challenges regarding craftsman regeneration and the necessity to adapt to global market demands without losing its distinctive identity. This research aims to identify craftsman creativity patterns, examine the aesthetic depth of motifs, and analyze functional transformations in Ramayana reliefs in Tigajuru. The findings are expected to provide strategic recommendations for the future preservation of the carving industry. The method employed is a qualitative-descriptive approach with a case study design using observation, in-depth interviews, and documentation. Data analysis was conducted interactively using the Miles, Huberman, and Saldana model. The results indicate that craftsman creativity is manifested in the mastery of flexible carving techniques, despite technical quality inconsistencies serving as a form of non-linear expression. The aesthetic value of these motifs stems from the blend of Ramayana figurative icons with stylized flora and fauna, creating a harmonious visual narrative. Furthermore, a significant functional transformation was found, shifting from decorative door elements into visual media communicating moral values and deep cultural identity. In conclusion, these skill dynamics and shifts in utility prove that relief carvings serve not only as physical artifacts (artifact) but also as carriers of philosophical symbolism (mentifact) relevant to the contemporary cultural context.